Outcome after medial unicompartmental knee replacement - Gulati, A (2013)
Medial Oxford unicompartmental knee replacement (UKR) is an established and successful treatment for patients with antero-medial knee osteoarthritis. However, following the operation some patients have pain which compromises their functional outcome. The aims of this thesis were to determine the incidence of pain, to identify the patient, disease and surgical risk factors associated with this pain and to try and understand why it occurs. The clinical studies were performed using patients operated on by experienced surgeons. The incidence of post-operative severe pain was 3% at six weeks and 2% at one year and the incidence remained unchanged at subsequent follow ups. The overall incidence of pain has reduced over the years. In patients who had UKR between 1998 and 2001, the incidence of severe pain was 5%; this reduced to 2.3% for the period between 2008 and 2011. As the indications have not changed, the improvement is probably due to modifications in the surgical technique and due to improvements in instrumentation. Patients with severe pain at the final follow up had a worse neuropathic pain score, and the patients with possible pre-operative neuropathic pain achieved significantly worse outcome. To explore the effect of disease severity on outcome, matched cohorts of patients with partial thickness cartilage loss (PTCL), bone-on-bone and bone loss were compared. All those with bone-on-bone and bone loss did well, whereas 20% of those with PTCL did not benefit from the surgery; 7% had severe pain and 17% had pain related complications. Although component and leg alignment, and component overhang have a profound effect on the outcome of total knee replacement (TKR), their effect on the outcome of the Oxford UKR are not known. It was found that malalignment in the coronal or sagittal planes of the femoral component within ±10° and of the tibial component within ±5° did not compromise the outcome. Leg alignment was not related to outcome even though 18% were in 5° varus and 8% were in 10° varus. In contrast, tibial component overhang ≥3 mm compromised the outcome and 21% of these patients continue to suffer from pain. The presence of radiolucent lines (RLL) following a joint replacement is usually deemed to be indicative, or predictive, of loosening. 63% of Oxford UKRs were found to have RLL under the tibial component. No correlation was found between RLL and outcome, particularly pain. It has been suggested that post-operative pain, which is commonly antero-medial over the proximal tibia, may be related to bone overload. This was explored using the finite element (FE) analysis. Following implantation of the Oxford UKR, the strains in the antero-medial region doubled. Various implantation, loading and alignment variables were studied and the findings correlated with the clinical studies, suggesting that high strain is an important cause of pain. With time, the bone will remodel, so the strains will decrease but individual differences in the remodeling threshold may explain resolution of symptoms in some, but not in all, patients. In conclusion, this work has shown that following the Oxford UKR, pain is a rare but important complication. The chance of pain can be decreased by operating only on patients with bone-on-bone arthritis and taking care with the surgical technique. Bone overload is likely to be an important cause of pain, and further modification to the implant or technique, such as achieving fixation of the tibial component vertical wall to bone, may further decrease the incidence of pain.